Compact Passively Q-Switched Tm:KY(WO4)2 Laser - V. E. Kisel (Приборы и методы измерений)
Diode-pumped thulium lasers emitting in the spectral range near 2 μm are attractive for applications in different areas: surgery, rangefinding, and environmental atmosphere monitoring. In this article the latest results of Tm:KYW laser performance with a polycrystalline Cr:ZnSe as the most available saturable absorber for 2 μm spectral region are presented.A maximum continuous-wave output power of ≈ 0.65 W with a slope efficiency of 55 % was obtained at the wavelength of 1940 nm. Laser pulses with energy of 26 μJ and repetiotion rate of 6 kHz coresponding to 156 mW of average output power at 1910 nm were obtained at 2.2 W of incident puwp power for the Cr:ZnSe saturable absorber with initial transmission of 95 %. By using of saturable absorber with lower initial transmission of 90 % laser pulses with energy of 40 μJ and duration as short as 10 ns were realized. The maximal pulse repetition rate was 2.8 kHz at incident pump power of 2.2 W.Based on the obtained results, it can be concluded that Tm:KYW crystals are promising active media for the compact passively Q-switched lasers emitting in the spectral range near 2 μm for the usage in surgery and rangefinding. Also, described laser is planned to be used as a laser source in laser-induced damage threshold measurements setup for investigation of damage threshold of saturable absorbers as well as nonlinear crystals at the wavelength near 2 μm.